Climatic water balance for AI-Ruhba District in Najaf Governor – Iraq - AI-Haider, Mariam A.; AI-Kubaisi, Qusai Y. (Iraqi Journal of Science, 2025)
The study area is situated in the southwest of the governorate of Najaf, underwent a climatic analysis using data from Al-Najaf Meteorological Station spanning from 1980 to 2022. Findings reveal an annual rainfall of 134.2 mm, a relative humidity of 40.32%, an average temperature of 25.6°C, a wind speed of 1.52 m/sec, 8.45 hours of daily sunshine, and an evaporation rate of 5470.4 mm. Notably, The total amount of corrected evapotranspiration was 1038.75 mm. Water Surplus (WS) varies across months, with values of 6.59 mm (November), 30.11 mm (December), 11.93 mm (January), and 4.72 mm (February). The water surplus amounted to 53.35 mm, about 39.75% of the annual rainfall. This value represents the portion of rainfall that recharges groundwater, assuming no surface runoff in the study area. However, factors such as evaporation and plant uptake can reduce the actual amount of water that infiltrates the soil. The silty sand soil type and low rainfall contribute to limited surface runoff.